Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw dalam Meningkatkan Kemampuan Pemahaman dan Komunikasi Matematis Siswa Sekolah Menengah Atas - Fona Fitry Burais; Hajidin Hajidin; Said Munzir (Universitas Syiah Kuala, 2015)
The mathematical ability that should be owned by the students as stated by the NCTM, namely (1) learn to communicate; (2) learn to reason; (3) learn to solve problems; (4) learn to associate ideas; (5) learning to represent ideas. By having the ability mathematical understanding, students are able to explain the relationship between concepts and is able to communicate ideas with symbols, tables, diagrams, or other media to clarify the issue and was able to solve the problems. It is thus necessary that the proper application of learning models to improve the understanding and communication of mathematical students is one model of cooperative jigsaw. This study aims to determine the increase in the ability of students 'mathematical understanding and communication that derive jigsaw cooperative learning with students who received conventional teaching students to be reviewed as a whole and by the beginning of students' mathematical abilities. This research used experimental design with pretest-posttest control group design. Samples selected by random sampling consisted of two classes, namely classes and class XMIA5 XMIA2. Collecting data using test instruments mathematical understanding and communication capabilities that pretest and posttest in the second grade. hypothesis testing using t-test, t test